2014
DOI: 10.1002/stc.1635
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic optimization of shape-memory-alloy rubber bearing (SMARB) for isolating buildings against random earthquake

Abstract: SUMMARY Shape‐memory‐alloy (SMA) aided isolation bearing has been proposed recently in order to achieve improved performances in several aspects, comparing the traditional bearings for isolation. The behavior of such system has been experimentally demonstrated and numerically simulated under recorded seismic ground motions. The present work deals with the study of optimum performance of SMA‐based isolation system under random earthquake. The stochastic response evaluation of the isolated building is performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 40 publications
(61 reference statements)
0
14
0
Order By: Relevance
“…Performances of SMA assisted rubber bearing was evaluated by Ozbulut and Hurlebaus [30] for protecting highway bridges against near-field earthquakes and also compared with those of the SMA-based sliding isolation system. Superior performance of SMA supplemented rubber bearing over the elastomeric bearing was studied for the seismic vibration control of structures by Gur et al [31] and Das and Mishra, [32] and a stochastic structural optimization study was also carried out by Gur et al [33] Noting the additional energy dissipation and recentering capacity of SMA in seismic vibration control, the present study attempts to investigate the effectiveness of SMAassisted rubber bearing, that is, SMARB for vibration control of building structures subjected to BIGM. The performance is evaluated with regard to maximum acceleration and isolator displacement obtained by nonlinear time history analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Performances of SMA assisted rubber bearing was evaluated by Ozbulut and Hurlebaus [30] for protecting highway bridges against near-field earthquakes and also compared with those of the SMA-based sliding isolation system. Superior performance of SMA supplemented rubber bearing over the elastomeric bearing was studied for the seismic vibration control of structures by Gur et al [31] and Das and Mishra, [32] and a stochastic structural optimization study was also carried out by Gur et al [33] Noting the additional energy dissipation and recentering capacity of SMA in seismic vibration control, the present study attempts to investigate the effectiveness of SMAassisted rubber bearing, that is, SMARB for vibration control of building structures subjected to BIGM. The performance is evaluated with regard to maximum acceleration and isolator displacement obtained by nonlinear time history analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Performances of SMA assisted rubber bearing was evaluated by Ozbulut and Hurlebaus for protecting highway bridges against near‐field earthquakes and also compared with those of the SMA‐based sliding isolation system. Superior performance of SMA supplemented rubber bearing over the elastomeric bearing was studied for the seismic vibration control of structures by Gur et al and Das and Mishra, and a stochastic structural optimization study was also carried out by Gur et al…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results demonstrated that the dampers were effective in reducing both the peak and residual deformation of the structure subjected to strong earthquakes. Apart from damping systems, SMAs have also been considered in other seismic resistant devices and members, including braces, beam‐to‐column connections, base isolators, and bridges …”
Section: Introductionmentioning
confidence: 99%
“…The experimental results demonstrated that the dampers were effective in reducing both the peak and residual deformation of the structure subjected to strong earthquakes. Apart from damping systems, SMAs have also been considered in other seismic resistant devices and members, including braces, [14][15][16][17] beam-to-column connections, [18][19][20][21][22][23][24] base isolators, 25,26 and bridges. 27,28 Although the wire form of SMA has proven to be effective in providing energy dissipation and self-centring capability, there are still practical issues such as difficulty of gripping (especially when a large number of wires are to be included) and vulnerability to fracture at the gripping region due to local stress concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Further, SMA springs consisting of pseudo‐elastic SMA wires and helical SMA springs (in isolation system) have been used for the passive seismic vibration control of civil structures. Also, SMAs have been combined with rubber bearings for reducing the displacement of isolator bearings and have been supplemented with sliding isolators for developing super‐elastic friction base isolators. Finally, SMAs have demonstrated superior control efficiency in protecting highway bridges and buildings from near‐fault earthquakes .…”
Section: Introductionmentioning
confidence: 99%